Internal combustion engines : Applied thermosciences - Ferguson, Colin R. (John Wiley and Sons, 2016)
Introduction to internal combustion engines - Heat engine cycles - Fuel, air and combustion thermodynamics - Fuel-air combustion processes - Intake and exhaust flow - Fuel and airflow in the cylinder - Combustion processes in engines - Emissions - Fuels - Friction and lubrication - Heat and mass transfer - Engine testing and control - Overall engine performance - Appendices.